The Strategi Pemerintah Lampung Barat dalam Menjaga Kearifan Lokal - Aprilia Lestari; Martharia Putri Utami Tanjung; Evi S. B. Utami (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2025)
The local wisdom of the Sekura tradition is an important cultural identity of the West Lampung community, but faces quite significant challenges in the context of modernization. These challenges include decreasing interest of the younger generation, the entry of popular culture causing a shift in values, and the pressure of commercialization, which poses a risk of reducing the original meaning of the Sekura tradition. Therefore, this study aims to analyze the strategy implemented by the West Lampung Regency Government to preserve the local wisdom of Sekura. A descriptive qualitative method was used to analyze the strategy implemented by the West Lampung Regency Government, in line with Wheelen & Hunger strategy theory. The results showed that the preservation of the Sekura tradition in West Lampung Regency occurred through regional policies, including development of cultural studios, integration of educational curricula, organization of festivals, strengthening of traditional institutions, and empowerment of creative economy. However, implementation still faces challenges, including regional inequality in support, limited cultural human resources, a lack of standardized teaching materials, and documentation that lacks professional coordination. This underscores the need to strengthen cross-party coordination, equalize facilities, and implement a sustainable mentoring strategy to preserve tradition for future generations. Keywords: Strategy; West Lampung Government; Local Wisdom; Local Culture; Sekura Tradition